The Association of Aberrant Expression of FGF1 and mTOR-S6K1 in Colorectal Cancer - Duan, Tinghui; Zhou, Diyuan; Yao, Yizhou; Shao, Xinyu (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most frequent malignant neoplasms worldwide, and the effect of treatments is limited. Fibroblast growth factor 1 (FGF1) has been involved in a wide variety of several malignant diseases and takes part in the tumorigenesis of CRC. However, the function and mechanism of FGF1 in CRC remains elusive. In this study, the results indicated that FGF1 is elevated in CRC tissues and linked with poor prognosis (P < 0.001). In subgroup analysis of FGF1 in CRC, regardless of any clinic-factors except gender, high level FGF1 expression was associated with markedly shorter survival (P < 0.05). In addition, the expression of p-S6K1 and FGF1 was not associated in normal tissue (P = 0.781), but their expression was closely related in tumor tissue (P = 0.010). The oncogenic role of FGF1 was determined using in vitro and in vivo functional assays. FGF1 depletion inhibited the proliferation and migration of CRC cells in vitro and vivo. FGF1 was also significantly correlated with mTOR-S6K1 pathway on the gene and protein levels (P < 0.05). In conclusion, FGF1 acts as a tumor activator in CRC, and against FGF1 may provide a new visual field on treating CRC, especially for mTORC1-targeted resistant patients.